2009
DOI: 10.1109/tnsre.2008.2008285
|View full text |Cite
|
Sign up to set email alerts
|

Medial Gastrocnemius Myoelectric Control of a Robotic Ankle Exoskeleton

Abstract: A previous study from our laboratory showed that when soleus electromyography was used to control the amount of plantar flexion assistance from a robotic ankle exoskeleton, subjects significantly reduced their soleus activity to quickly return to normal gait kinematics. We speculated that subjects were primarily responding to the local mechanical assistance of the exoskeleton rather than directly attempting to reduce exoskeleton mechanical power via decreases in soleus activity. To test this observation we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 28 publications
2
64
1
1
Order By: Relevance
“…We found that humans significantly reduced soleus recruitment when walking with a powered exoskeleton that acutely increased the gain between either soleus Kao et al 2010a) or gastrocnemius (Kinnaird and Ferris 2009) activation and the resulting plantar flexor torque. This resulted in total (human ϩ exoskeleton) ankle moments that were comparable to unassisted walking (Kao et al 2010a).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…We found that humans significantly reduced soleus recruitment when walking with a powered exoskeleton that acutely increased the gain between either soleus Kao et al 2010a) or gastrocnemius (Kinnaird and Ferris 2009) activation and the resulting plantar flexor torque. This resulted in total (human ϩ exoskeleton) ankle moments that were comparable to unassisted walking (Kao et al 2010a).…”
mentioning
confidence: 85%
“…This resulted in total (human ϩ exoskeleton) ankle moments that were comparable to unassisted walking (Kao et al 2010a). Subjects made both rapid adaptations to maintain ankle joint moments (Kao et al 2010b) and slower adaptations to minimize negative work produced by the exoskeleton Kinnaird and Ferris 2009). This research provides evidence that the human nervous system is proficient at making meaningful and independent adjustments to soleus and gastrocnemius activation profiles during gait in response to perturbations that disrupt the gain between a given efferent command and the resulting muscular output.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Ferris et al [6][7][8][9] built a pneumatically powered knee-ankle-foot orthosis, which was used to test this device's mechanical performance during human walking. Chu et al [10] proposed a hydraulically driven lowerlimb exoskeleton driving the hip, knee, and ankle joints to compensate for the strength and endurance of a human under a payload.…”
Section: Introductionmentioning
confidence: 99%
“…Slightly less invasive are approaches based on surface electromyography (EMG) [6]. The user intentions can be correlated with his/her EMG data using either model-based approach [7] or model-free approach [8]. EMG was also used for the control of the HAL-5 exoskeleton device in prediction of the motion [9] and for adjusting the impedance around the knee joint [10].…”
mentioning
confidence: 99%